Updating 2005 Purchasing Power Parities to 2009 in the Asia and Pacific Region: Methodology and Empirical Results - Yuri Dikhanov; Chellam Palanyandy; Eileen Capilit (Asian Development Bank (ADB), 2011)
Purchasing power parities (PPPs) estimated on an annual basis are used in many analyses and are highly demanded by researchers in various fields, ranging from poverty and comparative living standards, to competitiveness and military expenditures. However, the regular PPP exercises are conducted every 5–6 years, or even less frequently (12 years passed between the 1993 and 2005 exercises). The financial and human resources that go into a benchmark PPPs exercise are very significant. Hence, PPPs for nonbenchmark years are usually extrapolated using national accounts' deflators. This simplistic updating, however, results in outcomes that are not consistent with benchmark estimates, with the inconsistencies increasing as the year of extrapolation moves further away from the benchmark. This paper discusses alternative methods and approaches for estimating PPPs for nonbenchmark years in the Asia and Pacific region. Collectively called 2009 PPP Update, the methods and approaches constitute an extension of the 2005 PPP benchmark for the Asia and Pacific region, with additional data collected in 2009 and some interproduct and intracountry price correlations made against the 2005 exercise. The 2009 PPP Update concentrates on a core list of items for household consumption, and investment on machinery and equipment. The methodology to create a statistically efficient and reduced product list for the 2009 PPP Update is discussed. In most economies, prices are being collected in capital cities only and adjusted to the national levels using price data from consumer price indices (CPI) or other information. For gross fixed capital formation in construction, the paper suggests a simplified regression method. For government consumption, the same methodology as in the 2005 ICP was adopted.
hdl:11540/2049
Keywords: 330; Kaufkraftparität; Statistische Methode; Asiatisch-pazifischer Raum